Development of E-Module Flipbook Based on Discovery Learning to Increase Learning Motivation - Fitriyah, Isnanik Juni; Sahda, Salma Nur Salsabila (JIPVA (Jurnal Pendidikan IPA Veteran), 2023)
In the implementation of science learning, conventional teaching materials and lecture methods that are commonly used by teachers in schools have not been effective in increasing students' learning motivation. This study aims to develop e-module flipbooks based on discovery learning that are valid, practical, and effective in increasing learning motivation and knowing the completeness of student learning outcomes. The ADDIE model applied includes analyzing, designing, developing, implementing, and evaluating steps. Quantitative data were obtained from media and material validation tests, practical tests of teachers and students, and tests of the effectiveness of learning motivation and completeness of learning outcomes. The percentage of media and material validation test results obtained was 95.2% and 95.9%. The practicality test results for teachers and students were 93.5% and 84.4%. The paired sample t-test shows that there is a difference in learning motivation with sig. 0.000 the results of the N-gain test obtained moderate criteria and complete learning outcomes of 83%. Thus, the discovery of learning-based e-module flipbook products are valid, practical, and effective in increasing students' learning motivation and completing learning outcomes.